Hubungan Resiliensi Matematis dengan Komunikasi Matematis - Meilasari, Venty; Kurniawati, Kurniawati (Universitas PGRI Semarang, 2026)
Mathematical communication is a crucial student ability that remains insufficient in reality, necessitating supporting factors like mathematical resilience. This quantitative correlational study aims to examine the correlation between mathematical resilience and mathematical communication skills among Grade X students at SMK Negeri 2 Kotabumi in the 2025/2026 Academic Year. From a population of 277 students, a sample of 75 was selected using a proportional random sampling technique based on the Slovin formula with a 10% error tolerance. Data were collected via a mathematical resilience questionnaire and a mathematical communication skills test. Data analysis techniques included the Lilliefors normality test and the Rank Spearman correlation test. The normality test showed that the mathematical resilience data were normally distributed, while the communication skills data were not. Therefore, hypothesis testing shifted to non-parametric statistics using the Rank Spearman correlation test. The analysis yielded a correlation coefficient of 0.458 (moderate category) with an adequate significance value, leading to the rejection of the null hypothesis () and acceptance of the alternative hypothesis ().In conclusion, there is a positive and significant correlation between students' mathematical resilience and their mathematical communication skills. An increase in students' mathematical resilience will be followed by a tendency to improve their mathematical communication skills